2011
DOI: 10.4061/2011/151656
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cellulase Activity from a New Strain ofBacillus subtilisby Medium Optimization and Analysis with Various Cellulosic Substrates

Abstract: The cellulase activity of Bacillus subtilis AS3 was enhanced by optimizing the medium composition by statistical methods. The enzyme activity with unoptimised medium with carboxymethylcellulose (CMC) was 0.07 U/mL and that was significantly enhanced by CMC, peptone, and yeast extract using Placket-Burman design. The combined effects of these nutrients on cellulase activity were studied using 22 full factorial central composite design. The optimal levels of medium components determined were CMC (1.8%), peptone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 28 publications
9
57
0
3
Order By: Relevance
“…These results showed that the optimum growth temperature of 36 o C for achieving high b-glucosidase activity is typical for T. harzianum, consistent with previous findings [35,36]. It is known that b-glucosidase activity tends to vary under different culture temperatures and is strain dependent as well [37].…”
Section: Effect Of Temperature and Carbon Sourcesupporting
confidence: 91%
“…These results showed that the optimum growth temperature of 36 o C for achieving high b-glucosidase activity is typical for T. harzianum, consistent with previous findings [35,36]. It is known that b-glucosidase activity tends to vary under different culture temperatures and is strain dependent as well [37].…”
Section: Effect Of Temperature and Carbon Sourcesupporting
confidence: 91%
“…Studies using cellulase producing fungal isolates have shown importance of K 2 HPO 4 in cellulase production. Elimination of K 2 HPO 4 from culture condition has been observed to reduced cellulase production using Trichoderma reesei 16 , while incorporating K 2 HPO 4 in culture medium along with other essential components has been shown to increase cellulase production by several times using Clostridium thermocopriae 17 and Trichoderma reesei 18 . With bacterial isolates K 2 HPO 4 being component of media composition, studies by Deka et al 18 , Gururaj 19 and Shankar et al 20 show no significant impact of K 2 HPO 4 on cellulase production.…”
Section: Resultsmentioning
confidence: 99%
“…Elimination of K 2 HPO 4 from culture condition has been observed to reduced cellulase production using Trichoderma reesei 16 , while incorporating K 2 HPO 4 in culture medium along with other essential components has been shown to increase cellulase production by several times using Clostridium thermocopriae 17 and Trichoderma reesei 18 . With bacterial isolates K 2 HPO 4 being component of media composition, studies by Deka et al 18 , Gururaj 19 and Shankar et al 20 show no significant impact of K 2 HPO 4 on cellulase production. The present study using Pseudomonasbalearica as a highest cellulase producing bacterial isolate indicates the importance of combine effect of K 2 HPO 4 and cellulose on cellulase production, where increasing concentration of K 2 HPO 4 and cellulose significantly increase the enzyme production two fold.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been carried out to investigate the endoglucanase activity of similar aerobic bacteria. For instance, the maximum CMCase activity of Bacillus subtilis AS3 was found to be 0.43 IU/mL (Deka et al, 2011). Gupta et al (2012) isolated several cellulose-degrading bacteria exhibiting CMCase activities in the range of 0.162-0.400 IU/mL.…”
Section: Endoglucanase Activitymentioning
confidence: 99%